The effect of low inclusion levels of Antarctic krill (Euphausia superba) meal on growth performance, apparent digestibility and slaughter quality of Atlantic salmon (Salmo salar). (25th June 2016) - Hatlen, B.; Berge, K.; Nordrum, S.; Johnsen, K.; Kolstad, K.; Mørkøre, T.
Abstract: Two trials with Atlantic salmon ( Salmo salar ) were conducted to evaluate the potential of krill meal to improve feed intake. In the first experiment, after transfer to sea water, salmon smolts were fed diets added 75 or 150 g kg −1 Antarctic krill meal in substitution for fish meal for 13 weeks. The apparent digestibility coefficient for crude protein and the majority of the amino acids was significantly lower in the feeds added krill meal (around 83.5%) than in the control diet (84.9%), whereas the digestibility of crude lipids, dry matter and energy was not significantly different among the three diets. Krill meal addition resulted in higher feed intake, which led to higher growth rates and final body weights. In the second experiment, large salmon were fed a diet containing 100 g kg −1 krill meal for 6 weeks before slaughter. Their feed intake and growth performance were assessed, and fillet and visceral fat contents were measured. Salmon fed the 100 g kg −1 krill meal diet tended to eat more, resulting in significantly increased growth rates, when compared to control fish. Fish fed krill meal also had a significantly lower condition factor.